Evaluation of Office Ligation in the Treatment of Hemorrhoids at Nepalgunj Medical College Teaching Hospital - Ansari, Meraj Alam; Mishra, Satindra Mohan; KC, Binaya (Journal of Nepalgunj Medical College, 2017)
Introduction: Rubber band ligation, an outpatient procedure for treatment of 2nd and 3rd degree hemorrhoids is an effective mode of management. Aims and objectives: To evaluate the effectiveness of rubber band ligation as an office procedure in the treatment of 2nd and 3rd degree hemorrhoids. Material and Methods: This is a cross sectional hospital based study of 30 cases that underwent rubber band ligation as an outpatient procedure for 2nd and 3rd degree hemorrhoids done in Nepalgunj Medical College Teaching Hospital from the period of August 2014 to June 2015. The patients were followed up for six months for the development of procedure related complications, relief of symptoms, and requirement of any further interventions. The total cost of treatment was calculated and the time off work was noted. Patients were requested to assess the forms of treatment as excellent, moderately successful or of little help based on their results post treatment. Statistical analysis using SPSS software (version 20) was done and p value less than 0.05 was taken as significant. Results: Post procedure complications were milder and self-limiting, with discomfort in 57.5% (2nd degree) and 60% (3rd degree), pain in 5% (2nd degree) 40% (3rd degree), bleeding in 22.5% (2nd degree) and 30% (3rd degree) of patients with absence of any major complications (sepsis or death). Majority (77.5% in 2nd degree, 70% in 3rd degree) of the patients significantly improved after initial treatment with band ligation. Some of the patients treated by band ligation required further intervention i.e. 16.66% in 2nd and 16.66% in 3rd degree as repeat ligation in the immediate post-op period and were managed subsequently. But none of them required any surgical procedures. Majority of the patients treated by band ligation were able to resume their normal work within three day i.e. 95% in 2nd and 90% in 3rd degree hemorrhoids. Most of the patients spent Rs 2000- 2500 (52.5% in 2nd and 40% in 3rd degree) which most was on routine checkups and follow-ups but it was very cheaper as compared to others modalities. Most of the patients (77.5% in 2nd and 70% in 3rd degree) treated by band ligation assessed the treatment as excellent. Conclusion: Rubber band ligation is a simple, safe and effective method for treating symptomatic second and third degree hemorrhoids as an outpatient procedure with significant improvement in quality of life. Immediate relief of symptoms can be obtained in the post-operative period and therefore be considered as the treatment of choice for second and third degree hemorrhoid. Though the complications are slightly higher and improvement in symptoms were delayed than in second degree but still Rubber Band Ligation proved to be effective even in 3rd degree hemorrhoid. Journal of Nepalgunj Medical College Vol.13(1) 2015: 17-20